Identifikasi Bahaya Risiko Keselamatan dan Kesehatan Kerja pada Proses Operasional Coffee Shop (Studi Kasus: Janus Cafe Kota Batu) - Haryono, Putri Dwinita; Mursyid, Idham Yusuf Baihaqi; Wardani, Devika Ayu; Wirakusuma, Devina Ramadhanty; Nareswara, Zahra Filloa; Klarisa, Zahra; Sulistyorini, Anita (Universitas Negeri Malang, 2024)
One of the Food and Beverage industry sectors, namely Janus Coffee and Roastery located in Batu City, has a risk of hazards that often occur in its operational activities, starting from the process of preparing tools and raw materials to serving to customers. These risks include fatigue, minor to severe injuries, and even burns due to exposure to hot objects during the product manufacturing stage. This study aimed to identify, analyze, and assess the risk of hazards in the operations of Janus Coffee and Roastery in Batu City using the HIRADC (Hazard Identification, Risk Assessment and Risk Control) method. The object of research was all stages of the work process at Janus Cafe. The results of the analysis showed that there were 32 risks in the process of making raw materials to serve to customers with 4 high risk level risks, 17 medium risk level risks and 11 low risk level risks. Thus, through the existing risk factors, control efforts will be made, such as installing a cooker hood above the stove to suck hot steam to make work safety SOPs at the risk of hazards that often occur.